The struggle for inclusion: Muslim minorities and the democratic ethos - Ivarsflaten, Elisabeth (The University of Chicago Press, 2022)
"Europe has struggled with Muslim immigration. While opposition to such immigration has become increasingly vocal, in many places efforts have been made to help these immigrants integrate into society. In The Struggle for Inclusion: Muslim Immigrants and the Democratic Ethos, Elisabeth Ivarsflaten and Paul M. Sniderman shift the focus of scholarly work from those who are intolerant of immigrants to those who are tolerant and accept Muslim immigrants. The challenge is how do the tolerant reconcile their often liberal values with the conservative values held by many among the more conservative Muslim immigrants? How do liberal Europeans reconcile their values about, for example, the rights of women, with the conservative values on these issues held by many in the Muslim community? They find that a minority of Europeans are prejudiced against all Muslims, but many hold different feelings about conservative Muslims and their leadership because of conflicts with specific liberal values"--